Evaluation of the BACTEC MGIT 960 and the MB/BacT Systems for Recovery of Mycobacteria from Clinical Specimens and for Species Identification by DNA AccuProbe - Alcaide, Fernando (American Society for Microbiology, 2000)
A total of 120 mycobacterial isolates were recovered from 1,068 clinical specimens. Of these, 82.5% were in MGIT 960, 83.3% were in MB/BacT, 80% were in BACTEC 460, and 70% were on Löwenstein-Jensen medium. Mean times to detection of Mycobacterium tuberculosis (n = 96) were significantly shorter with MGIT 960 (12.6 days, P = 0.003) and BACTEC 460 (11.8 days, P < 0.001) than with MB/BacT (15.9 days). Although, MGIT 960 showed the lowest rate of recovery of M. kansasii genotype I (64.3%), the earliest growth was detected with this system (8.9 days). Low and similar rates of contamination were obtained with MGIT 960 (3.3%) and MB/BacT (3%). The AccuProbe test for identification showed excellent sensitivities with MGIT 960 (96.8%) and MB/BacT (100%) cultures. In addition to being nonradiometric, both MGIT 960 and MB/BacT are accurate, rapid, and labor-saving detection systems which could replace the radiometric method.